Reasonable adjustments for autistic clinicians: A qualitative study - Helen Smith; Sebastian C. K. Shaw; Mary Doherty; Jonathan Ives (PLoS ONE, 2025)
Autistic people experience barriers to accessing healthcare. Autistic clinical professionals may be able to help improve this situation. Previous research, however, has shown that Autistic clinical professionals experience numerous challenges in the workplace. If there is a ‘substantial’ and ‘long-term’ negative effect on the person’s ability to do normal daily activities, then Autism may be considered a disability under The Equality Act 2010; the jurisdiction of which covers Great Britain. Autistic clinical professionals working in healthcare settings across England, Wales, and Scotland are therefore entitled to reasonable adjustments to aid them in their clinical practice. This is a qualitative study. We recruited 82 Autistic clinical professionals via social media to complete an online survey. Questions broadly explored: 1) the challenges they faced in their clinical workplaces; and 2) the reasonable adjustments that they needed, had, or needed but did not have. Data were analysed quasi-thematically, also drawing on the principles of content analysis. Respondents reported multiple challenges from our analysis, from which we developed 8 themes: gaining and attending employment, reasonable adjustments under the radar, connecting and integrating (specifically, the communication mismatches between Autistic professionals and non-autistic colleagues, and fitting in socially and professionally), executive functioning, change, working environment, working practices/cultures, and the consequences and effects on Autistic clinical professionals). We recommend that Autistic clinical professionals and their employers individually discuss and iteratively revisit the unique combination of reasonable adjustments suitable for each person. In this way, employers may provide equitable workplaces for their staff which will benefit not only them, but their patients, and healthcare as a whole.